Building a self-balancing scooter II - Lim, Chze Wee (2015)
The purpose of this project is to design a self-balancing, two-wheeled scooter. With the introduction of another generation of students to work on the project, the goal was to further improve upon the design, or to redesign, the scooter developed so far. The issue of jerking was prominently the main issue to be solved. However, the presence of other complications has led to the troubleshooting to become far more complicated than initially suspected. After prolonged troubleshooting, testing, and isolating components of the device, a few core issues surfaced. Among the problems faced were hardware issues, such as noise affecting the microcontroller, as well as difficulty with programming a speed-controlled motor-controller. Even so, various improvements were made over the previous batch, though physically, little has changed in the device; the chassis used is still as before, the hub motors are reused, and the batteries are also carried over from the previous batch. The improvements made were, firstly, with regards to the circuit, the handle, and the program. The circuit is now more resistant to noise, though not impervious to it; the handle has easier access to the power button, and is easier to hold onto; and the program has better control algorithm, allowing more freedom on manipulating performance via gains. To conclude, it’s hoped that the information gathered thus far will help to improve the design further, as well as to overcome the problems that are still present.